2023
DOI: 10.1187/cbe.22-06-0108
|View full text |Cite
|
Sign up to set email alerts
|

Biology Instructors See Value in Discussing Controversial Topics but Fear Personal and Professional Consequences

Abstract: A national survey of biology instructors shows that instructors view the primary goal of science education as “understanding the world,” yet instructors hesitate to incorporate societally relevant content. This study addresses how an ideological awareness curriculum may bridge this gap and how instructor values and hesitancies affect teaching practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
0
9
1
Order By: Relevance
“…We found that there was no difference between the two sections with respect to the number or proportion of biological content included on the concept maps (Figure 4). One common instructor hesitancy to integrating societal content into the biology curriculum is that it will come at the expense of students' content knowledge (Levinson, 2006;Sadler et al, 2006;Herman et al, 2017;Tidemand and Nielsen, 2017;Beatty et al, 2023). However, our results show that while the ideologically aware class section learned more societal topics in biology, this did not come at the expense of biology content knowledge gained through the semester.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…We found that there was no difference between the two sections with respect to the number or proportion of biological content included on the concept maps (Figure 4). One common instructor hesitancy to integrating societal content into the biology curriculum is that it will come at the expense of students' content knowledge (Levinson, 2006;Sadler et al, 2006;Herman et al, 2017;Tidemand and Nielsen, 2017;Beatty et al, 2023). However, our results show that while the ideologically aware class section learned more societal topics in biology, this did not come at the expense of biology content knowledge gained through the semester.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, the success of the ideological awareness curriculum used in our study could be due to the curriculum, the active learning format in which it was taught, or a combination. However, traditional course content rarely makes the explicit connections to society made by our ideologically aware curriculum (Tanner and Allen, 2007;Nielsen, 2020;Beatty et al, 2023), and students are often unable to make connections between science and society without explicit instruction (Hofstein et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a previous study where introductory biology students did not understand how science impacts social issues ( 10 ). The limited exposure to social issues in biology courses may be due to a number of barriers including instructor confidence, curriculum priorities, and perceptions of students ( 27 , 28 ). Instructors may feel they lack the necessary knowledge and training to effectively integrate these issues into their curriculum ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The limited exposure to social issues in biology courses may be due to a number of barriers including instructor confidence, curriculum priorities, and perceptions of students ( 27 , 28 ). Instructors may feel they lack the necessary knowledge and training to effectively integrate these issues into their curriculum ( 27 , 28 ). Instructors may also struggle with prioritizing social issues in a curriculum where scientific content is primarily emphasized and highly valued ( 27 ).…”
Section: Discussionmentioning
confidence: 99%